Cheap, Pliable, and Disposable: The Entanglement of Waste Reclaimers and Plastics in the Global South - Loots, Olivia (Environmental ethics, 2025)
Informal waste reclaimers contribute significantly to waste management globally. Yet, their lives and labor are influenced by various environmental, social, and spatial injustices with roots in racist and exclusionary colonial systems. Using post-apartheid South Africa as an example from the Global South, a new materialist reading of the interaction between black waste reclaimers and plastics as recyclable material is presented in this article. The central argument is that the harms these workers are exposed to, and the recycling industry at large are underpinned by the racist and colonial practices, which render them disposable under capitalism. Foregrounding such instances of environmental racism serves as a corrective to the absence of sustained engagement with race in new materialist writings. While the new materialisms criticize human/nonhuman dichotomies, the category of "the human" remains largely intact. Waste disproportionately affects marginalized black bodies, and understanding such violent relations is vital in addressing environmental destruction in the twenty-first century.